Triglyceride glucose and haemoglobin glycation index for predicting outcomes in diabetes patients with new-onset, stable coronary artery disease: a nested case-control study. (3rd October 2018) - Jin, Jing-Lu; Sun, Di; Cao, Ye-Xuan; Guo, Yuan-Lin; Wu, Na-Qiong; Zhu, Cheng-Gang; Gao, Ying; Dong, Qiu-Ting; Zhang, Hui-Wen; Liu, Geng; Dong, Qian; Li, Jian-Jun
Abstract: Aim: Previous studies have shown that both triglyceride glucose (TyG) and haemoglobin glycation indexes (HGI) are predictors of cardiovascular risk. However, the prognostic value of TyG index and HGI in patients with type 2 diabetes mellitus (T2DM) and stable coronary artery disease (CAD) is not determined. Methods: We conducted a nested case-control study among 1282 T2DM patients with stable CAD. Patients were followed up for 3846 person-years. A total of 160 patients with events (12.5%) were identified and matched individually on age, gender, previous use of lipid lowering agents and duration of follow-up with 640 controls. Results: In Kaplan–Meier analysis, the upper tertiles of TyG index and HGI had a significant lower event-free survival ( p  = .002; p  = .036, respectively). Of the note, both TyG index and HGI were associated with increased risk of MACCEs after adjusting for confounding risk factors [adjusted HR (95% CI): 1.693 (1.238–2.316); 1.215 (1.046–1.411), respectively]. Moreover, adding TyG index to the Cox model increased the C-statistic to 0.638 (95%CI: 0.595–0.683, p  = .002) while the C-statistic was not statistically improved when HGI was included ( p  = .240). Conclusions: Both TyG index and HGI could predict cardiovascular outcomes in T2DM patients with new-onset, stable CAD while TyG index might be better. Key messages: Both TyG and HGI are predictors of cardiovascular risk. The prognostic value of TyG index and HGI in T2DM patients with stable coronary artery disease is not determined. Our study firstly indicates that TyG index might have better prognostic value than HGI in T2DM patients with new-onset, stable CAD.